WAR, SOCIOLOGY AND SOCIOLOGY OF WAR. THEORETICAL REVISION AND METHODOLOGICAL CONTRIBUTIONS - Gallegos, Claudio (2020)
The changes in the forms of war, since the end of the 20th century, show the necessity to establish a new theory that would allow to understand these new forms. This article seeks to collaborate with the process of reviewing and building knowledge of war from the field of sociology. For this, an exhaustive bibliographic review is conducted, which exposes new contributions that divert from the liberal production, which tends not to consider the war as a social phenomenon of important significance.